"Shock" Septic: II Clinical experience in Obstetrics and Gynecology - Gonzales Enders, Rodolfo (2015)
This study includes twenty-six cases of patients who developed septic shock in the Department of Obstetrics and Gynecology, General Hospital "Cayetano Heredia" and who were diagnosed and treated according to a preset scheme. The incidence of infections and septic shock for different patient groups gathered as 105 procedures that underwent set. The importance of septic abortion as the main cause of septic shock is highlighted. Emphasis is given to the importance of a therapeutic regimen based on the pathophysiology of shock. The microorganisms that cause endotoxemia are mainly gram-negative Escherichia coli and Klebsiella Aerobacter. Because most successful surgical treatment survival variable amplitude recommend but applied early, to remove the source of infection as soon as possible. The most important characteristics of the group studied, such as age, parity, predisposing factors, commitment to organ systems, mortality and causes that favored and pathology are described.